(untitled) (Annals of Medical Research, 2021)
Aim: There is a growing awareness of the association between physical and sexual abuse and subsequent development of psychopathology, but little is known about the prevalence and long-term effects of childhood abuse in bipolar disorder. The aim of this study was to investigate the relationship between childhood abuse and adult bipolar disorder. Material and Methods: 50 female and 42 male bipolar I or II disorder out-patients who were in remission were evaluated. Demographic data, comorbid Axis 1 disorder, history of childhood abuse, family history, suicide attempts and social factors that are associated with the course of illness were investigated.Results: Childhood abuse was reported in 54.3% of the bipolar patients in this study. The incidence of abuse was higher in women. While women were exposed to more sexual abuse, physical abuse was more common in men. The most common type of abuse was neglect. There was no significant difference in sociodemographic variables and family characteristics between patients with history of abuse and patients without history of abuse. Patients who endorsed a history of physical and sexual abuse and neglect compared with those who did not, had an earlier onset of bipolar illness, a higher rate of combined pharmacotherapy and increased number of comorbid disorders, especially post-traumatic stress disorder(PTSD).Conclusion: Greater appreciation of the relationship between early traumatic experiences and an adverse course in bipolar disorder should lead to preventive and early intervention measures that may reduce the associated risk of a poor outcome.